Young-onset type 2 diabetes families are the major contributors to genetic loci in the Diabetes UK Warren 2 genome scan and identify putative novel loci on chromosomes 8q21, 21q22, and 22q11. - Frayling, T; Wiltshire, S; Hitman, G; Walker, M; Levy, J; Sampson, M; Groves, C; Menzel, S; McCarthy, M; Hattersley, A (2003)
A young onset of type 2 diabetes is likely to result, in part, from greater genetic susceptibility. Young-onset families may therefore represent a group in which genes are more easily detectable by linkage. To test this hypothesis, we conducted age at diagnosis (AAD) stratified linkage analyses in the Diabetes UK Warren 2 sibpairs. In the previously published unstratified analysis, evidence for linkage (logarithm of odds [LOD] >1.18) was found at seven loci. The LOD scores at these seven loci were higher in the 245 families with AAD <55 years (L55) compared with the 328 families with AAD >55 years (G55). Five of these seven loci (1q24-25, 5q13, 8p21-22, 8q24.2, and 10q23.2) had LOD scores >1.18 in the L55 subset but only one (8p21-22) did in the G55 subset. Two additional loci (8q21.13 and 21q22.2) showed evidence for linkage in the L55 subset alone. Another locus (22q11) showed evidence for linkage in a subset of families with AAD <45 years. Using a locus-counting approach, the L55 subset had significantly more loci (P approximately 0.01) than expected under the null hypothesis of no linkage across the LOD score range 0.59-3.0. In contrast, the G55 subset contained no more susceptibility loci than that expected by chance. In conclusion, young-onset families provide both disproportionate evidence for linkage to known loci and evidence for additional novel loci. Our data confirm our hypothesis that families segregating young-onset type 2 diabetes represent a more powerful resource for defining susceptibility genes by linkage.